Rama Mandir - Ghosh, Ayan (2023)
Rama Mandir was originally built by an ascetic, Ramdas Bawa. In 1918, it was reconstructed by a Khatri merchant, Bhawanai Mohanji, and a shikara was added over the garbagriha. Marble idols of Lord Ram, Lakshman, and Sita from the original temple are enshrined in the garbagriha. The pujari family who maintains the temple, live at the rear.